ISPC Qualitative Prioritization Exercise - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2015)
This brief note describes the initial steps taken by the ISPC between June and September 2015 towards developing a framework for qualitatively assessing relative priorities across the 45 unique sub-IDOs. It describes the results of two parallel efforts undertaken aimed at eliciting priorities from two distinct groups of CGIAR stakeholders.